Los bosques del futuro - (AHEC), American Hardwoods Export Council (Instituto de Ecología, A.C., 1995)
Some of the Forest conservation programs in the United States are reviewed and their guidelines for professional management highlighted. Private landowners and companies play a fundamental role in the continuous regeneration of forest resources. In the last thirty years, more trees have been planted by these two types of property holders than have been harvested. Among the most important initiatives is the Sustainable Forest Initiative (SFI), promoted by the American Forest & Paper Association. The great majority of forested land in the United States is included in this program. The guidelines of this program, Which are based on the definition of Sustainable Forestry adopted during the International Earth Conference (Rio de Janeiro), 1992), are described. A general outline of the SFI program is presented and the ecological obligations of hardwood consumers are emphasized.